An optimal k of kth MA-ARIMA models under AR(p) models. Issue 4 (21st April 2017) - Dawoud, Issam; Kaçıranlar, Selahattin
ABSTRACT: In this article, we discuss finding the optimal k of (i) k th simple moving average, (ii) k th weighted moving average, and (iii) k th exponential weighted moving average based on simulated autoregressive AR( p ) model. We run a simulation using the three above examining method under specific conditions. The main finding is that the optimal k = 4 and then k = 3. Especially, the fourth WMA ARIMA model, fourth EWMA ARIMA model, and third EWMA ARIMA model are the best forecasting models among others, respectively. For all the six real data reveal the similar results of simulation study.